2022
DOI: 10.1037/ser0000519
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to PTSD treatment dropout in veterans returning from the wars in Iraq and Afghanistan: A systematic review.

Abstract: Although treatment effectiveness among evidence-based psychotherapies (EBPs) for posttraumatic stress disorder (PTSD) has been well established, treatment dropout among veterans continues to be a concern within these treatments. Due to the uniqueness of the Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF)/Operation New Dawn (OND) veteran cohort, this article reviewed the literature examining factors contributing to treatment dropout from EBPs for PTSD among OEF/OIF/OND veterans. We conducted a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
(149 reference statements)
1
14
0
Order By: Relevance
“…Although the flexibility of telephone-based collaborative care would seem to address common treatment barriers by offering convenience and privacy, more tailored outreach efforts may be needed to make mental health interventions appealing to younger veterans (Keller & Tuerk, 2015). More intensive, massed interventions for PTSD may reduce treatment dropout for this population (Sciarrino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the flexibility of telephone-based collaborative care would seem to address common treatment barriers by offering convenience and privacy, more tailored outreach efforts may be needed to make mental health interventions appealing to younger veterans (Keller & Tuerk, 2015). More intensive, massed interventions for PTSD may reduce treatment dropout for this population (Sciarrino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of PTSD treatment dropout among veterans are varied (Berke et al, 2019; Hoge et al, 2014; Sciarrino et al, 2022). Sciarrino et al (2022) recently published a systematic review examining dropout from treatment among OEF, OIF, and Operation New Dawn veterans.…”
mentioning
confidence: 99%
“…Predictors of dropout included demographic, cognitive, psychological, practical, and treatment-related factors (e.g., treatment type, modality, and format). Specifically, consistent dropout predictors included younger age, substance use disorders, and scheduling conflicts due to family responsibilities, college, and employment (Sciarrino et al, 2022). Additional practical reasons for dropout may include transportation issues and appointment travel time and cost, mobility limitations, finances, childcare needs, employment constraints, and long wait times at local VAs (Morland et al, 2019; Peterson et al, 2018).…”
mentioning
confidence: 99%
“…Several quantitative studies have attempted to identify factors that predict Veterans dropping out of PTSD EBPs by examining both demographic (e.g., war era, sex, age) and baseline clinical variables (e.g., PTSD severity). Broadly speaking, quantitative studies have typically yielded mixed results about the impact of sociodemographic factors on dropout (DeViva, 2014; Eftekhari et al, 2013; Holder et al, 2019; Lamkin et al, 2019; Sciarrino et al, 2022) with the exception that younger age has repeatedly been associated with greater dropout (Garcia et al, 2011; Kehle-Forbes et al, 2016; Mott et al, 2014; Sciarrino et al, 2022). In regard to the clinical variables, such as baseline symptom severity and PTSD service connection, studies have also largely yielded mixed findings (Eftekhari et al, 2013; Garcia et al, 2011; Szafranski et al, 2019; Sciarrino et al, 2022).…”
mentioning
confidence: 99%
“…Broadly speaking, quantitative studies have typically yielded mixed results about the impact of sociodemographic factors on dropout (DeViva, 2014; Eftekhari et al, 2013; Holder et al, 2019; Lamkin et al, 2019; Sciarrino et al, 2022) with the exception that younger age has repeatedly been associated with greater dropout (Garcia et al, 2011; Kehle-Forbes et al, 2016; Mott et al, 2014; Sciarrino et al, 2022). In regard to the clinical variables, such as baseline symptom severity and PTSD service connection, studies have also largely yielded mixed findings (Eftekhari et al, 2013; Garcia et al, 2011; Szafranski et al, 2019; Sciarrino et al, 2022). For example, Holder et al (2019) found that higher self-blame cognitions protected against dropout from cognitive processing therapy (CPT), perhaps because of the effectiveness of this treatment on these cognitions, but this finding has not been yet been replicated.…”
mentioning
confidence: 99%